How surface topography relates to materials' properties. - Assender, H; Bliznyuk, V; Porfyrakis, K (2002)
The topography of a surface is known to substantially affect the bulk properties of a material. Despite the often nanoscale nature of the surface undulations, the influence they have may be observed by macroscopic measurements. This review explores many of the areas in which the effect of topography is macroscopically relevant, as well as introducing some recent developments in topographic analysis and control.